Medico Legal Aspect of Rape (TAJ: Journal of Teachers Association, 2010)
Rape is a serious sexual offence having social, psychological, physical and legal aspects of the problem. This study tried to evaluate the different aspects of profile of victims of rape cases. 76 rape victims were included in the study who attended in Forensic Medicine Department of Dhaka Medical College & Comilla Medical College for medico legal examination in the year 2006. Commonest age group of the rape victims were 16-20 years (55.26%). Getting sexual gratification was the main motive in most of the cases (73.68%), other motives were forceful marriage (6.58%), defamation (2.63%), etc. Unmarried girls (71.05%), low socio-economic back ground-poor (82.89%) and illiterate females (82.89%) were the main victim of rape. Improvement of socio economic condition and literacy may be effective weapons to fight against this problem of our country. DOI: 10.3329/taj.v22i1.5030 TAJ 2009; 22(1): 111-114